The Insurance Sector in Japan: An Overview and Environmental Analysis - Jinghua Guo (European Scientific Journal, ESJ, 2018)
Insurance is a sector which affects the public interest. The sustainable development of the insurance sector is directly related to the stability of the national financial system and has an impact on the political stability of the country. Although the bursting of Japanese economic bubble and insurance liberalization had a serious impact on the Japanese insurance sector in the 1990s, it is getting back to the right track in recent years. Under the loose monetary and low interest rate policies in Japan at present, what is the current competitive environment? And could the Japan’s insurance sector has a steady growth continually? This article based on Porter‘s Five Force Model and PEST Model to analyze the micro-environment and macro-environment of the Japan’s insurance sector and reveals its current situation and potential challenges. Findings portray the competition in Japanese insurance sector is assessed as moderate and mainly comes from industry rivalry. In both policy and economic level, the current situation has a negative impact on the Japanese insurance sector. Moreover, the interest rate sensitivity of non-life insurance is generally lower than that of life insurance. So the negative interest rate policy in Japan will seriously affect the development of the life insurance sector, while the non-life insurance sector has little influence.